Annual Incidences and Progressions of Myopia and High Myopia in Chinese Schoolchildren Based on a 5-Year Cohort Study - Li, Shi-Ming; Wei, Shifei; Atchison, David A.; Kang, Meng-Tian; Liu, Luoru; Li, He; Li, Siyuan; Yang, Zhou; Wang, Yipeng; Zhang, Fengju; Wang, Ningli (Investigative ophthalmology & visual science, 2022)
To determine the annual incidences and rates of progression of myopia and high myopia in Chinese schoolchildren from grade 1 to grade 6 and explore the possible cause-specific risk factors for myopia. From 11 randomly selected primary schools in Anyang city, central China, 2835 grade 1 students were examined with annual follow ups for 5 years. Students were invited to undergo a comprehensive examination, including cycloplegic autorefraction, ocular biometry, and standardized questionnaires. The mean spherical equivalent refraction decreased substantially from +0.94 ± 1.03 diopter (D) in grade 1 to -1.37 ± 2.08 D in grade 6, with rapid annual myopic shifts, especially for students in grades 3 through 6 (-0.51 to -0.59 D). The prevalence of myopia increased substantially, with the yearly incidence of myopia increasing from 7.8% in grade 1 and 2 to 25.3% in grades 5 and 6, and the incidence of high myopia increased from 0.1% to 1.0%. The 5-year incidence of myopia was lowest among children who has a baseline spherical equivalent refraction of greater than +2.00 D (4.4%), and increased to nearly 92.0% among children whose baseline spherical equivalent refraction was 0.00 to -0.50 D. The incidence of myopia was higher in children who had less hyperopic baseline refraction, two myopic parents, longer axial length, deeper anterior chamber, higher axial length-corneal radius of curvature ratio, and thinner lenses. Both the annual incidence and progression rates of myopia and high myopia were high in Chinese schoolchildren, especially after grade 3. Hyperopic refraction of children should be monitored before primary school as hyperopia reserve to prevent the onset of myopia and high myopia.